Pengaruh Leverage dan Profitabilitas Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi Pada Perusahaan Industri Sub Sektor Batu Bara di Indeks Saham Syariah Indonesia - YUNIANTY, RINA TRI (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2023)
This Research examines the balance between corporate growth and stability in a dynamic global economy, with a focus on the coal industry in the Indonesian Sharia Stock Index. Investigating factors such as leverage, profitability, and dividend policy, this study aims to understand firm value and how these variables interact, especially with dividends as a moderating variable. Hypothesis testing results show that Debt to Equity Ratio (DER) and Return on Asset (ROA) have no significant influence on firm value, and dividend policy is unable to moderate the relationship between these variables and firm value. These findings provide insight that these factors may not be the main determinants inassessing firm performance and value in the coal industry.